Fibrillin-1 mutant mouse captures defining features of human primary open glaucoma including anomalous aqueous humor TGF beta-2 - MinHee K. Ko; Jeong-Im Woo; Jose M. Gonzalez; Gayeoun Kim; Lynn Sakai; Janos Peti-Peterdi; Jonathan A. Kelber; Young-Kwon Hong; James C. Tan (Scientific Reports, 2022)
Abstract Primary open angle glaucoma (POAG) features an optic neuropathy, elevated aqueous humor (AH) TGFβ2, and major risk factors of central corneal thickness (CCT), increasing age and intraocular pressure (IOP). We examined Tight skin (Tsk) mice to see if mutation of fibrillin-1, a repository for latent TGFβ, is associated with characteristics of human POAG. We measured: CCT by ocular coherence tomography (OCT); IOP; retinal ganglion cell (RGC) and optic nerve axon counts by microscopic techniques; visual electrophysiologic scotopic threshold responses (STR) and pattern electroretinogram (PERG); and AH TGFβ2 levels and activity by ELISA and MINK epithelial cell-based assays respectively. Tsk mice had open anterior chamber angles and compared with age-matched wild type (WT) mice: 23% thinner CCT (p < 0.003); IOP that was higher (p < 0.0001), more asymmetric (p = 0.047), rose with age (p = 0.04) and had a POAG-like frequency distribution. Tsk mice also had RGCs that were fewer (p < 0.04), declined with age (p = 0.0003) and showed increased apoptosis and glial activity; fewer optic nerve axons (p = 0.02); abnormal axons and glia; reduced STR (p < 0.002) and PERG (p < 0.007) visual responses; and higher AH TGFβ2 levels (p = 0.0002) and activity (p = 1E−11) especially with age. Tsk mice showed defining features of POAG, implicating aberrant fibrillin-1 homeostasis as a pathogenic contributor to emergence of a POAG phenotype.